Coupling green hydrogen production to community benefits : A pathway to social acceptance? - Gordon, Joel A. ; 0000-0001-5000-5000; Balta-Ozkan, Nazmiye; Haq, Anwar; Nabavi, Seyed Ali (Energy Research & Social Science, 2024)
Hydrogen energy technologies are forecasted to play a critical supporting role in global decarbonisation efforts, as reflected by the growth of national hydrogen energy strategies in recent years. Notably, the UK government published its Hydrogen Strategy in August 2021 to support decarbonisation targets and energy security ambitions. While establishing techno-economic feasibility for hydrogen energy systems is a prerequisite of the prospective transition, social acceptability is also needed to support visions for the ‘hydrogen economy’. However, to date, societal factors are yet to be embedded into policy prescriptions. Securing social acceptance is especially critical in the context of ‘hydrogen homes’, which entails replacing natural gas boilers and hobs with low-carbon hydrogen appliances. Reflecting the nascency of hydrogen heating and cooking technologies, the dynamics of social acceptance are yet to be explored in a comprehensive way. Similarly, public perceptions of the hydrogen economy and emerging national strategies remain poorly understood. Given the paucity of conceptual and empirical insights, this study develops an integrated acceptance framework and tests its predictive power using partial least squares structural equation modelling. Results highlight the importance of risk perceptions, trust dynamics, and emotions in shaping consumer perceptions. Foremost, prospects for deploying hydrogen homes at scale may rest with coupling renewable-based hydrogen production to local environmental and socio-economic benefits. Policy prescriptions should embed societal factors into the technological pursuit of large-scale, sustainable energy solutions to support socially acceptable transition pathways.
Keywords: Domestic hydrogen acceptance; Energy transitions; Green hydrogen; Hydrogen economy; Importance-performance map analysis; Partial least squares structural equation modelling